Dielectric medium and laminated electronic component

By forming a special combination of biased analysis and pores in the electronics, the problem of cracks and defects in the electronics is solved, and sintering, insulation resistance and durability are improved.

CN119381165APending Publication Date: 2025-01-28TDK CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202410815929.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-07-26
Filing Date
2024-06-24
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to avoid cracks or defects in the dielectric, affecting its sintering properties, insulation resistance and durability.

Method used

By forming a biased analysis and a special combination of pores at the cross section of the electronics, ensure that the diameter of the pores is less than the diameter of the analytical analysis, and the average diameter ratio of partial analysis and pores is between 1.00 and 6.00, increasing the sintering and insulating performance of the electrical medium.

Benefits of technology

Effectively improve the sintering, insulation resistance and durability of the electrical media, reduce the production of cracks, and enhance its overall performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119381165A_ABST
    Figure CN119381165A_ABST
Patent Text Reader

Abstract

The invention provides a dielectric comprising dielectric particles, segregation, and pores. And a special combination of segregation and pore connection exists at the section.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a dielectric and a laminated electronic component. Background Art

[0002] The invention related to a laminated ceramic capacitor is described in Patent Document 1. Furthermore, a sintering aid component including Si is segregated in voids formed in a conductor forming region.

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Laid-Open No. 2004-273975 Summary of the invention

[0006] Technical problem to be solved by the invention

[0007] The present invention provides a dielectric material that is unlikely to be cracked or chipped, and a laminated electronic component including the dielectric material.

[0008] Technical solutions to the problem

[0009] In order to achieve the above-mentioned object, the dielectric of the present invention,

[0010] Contains dielectric particles, segregation and pores,

[0011] At the cross section, there is a special combination of the segregation and the pores meeting.

[0012] The diameter of the pores of the specific combination may also be smaller than the diameter of the segregation of the specific combination.

[0013] The value obtained by dividing the average diameter of the segregation by the average diameter of the pores may be greater than 1.00 and not more than 6.00.

[0014] The number ratio of the special combination at the cross section of the dielectric can also be 2.0×10 4 Pieces / mm 2 Above and 5.0×10 6 Pieces / mm 2 the following.

[0015] The linear expansion coefficient of the segregation may be smaller than the linear expansion coefficient of the dielectric particles.

[0016] In addition to O, Ca, Sr, Zr, and Ti, the element contained most in the segregation on the basis of atomic number may be Si.

[0017] The particle diameter of the dielectric particles may be greater than or equal to 0.10 μm and less than or equal to 3.00 μm.

[0018] The dielectric particles may also include a composition formula [(Ca x Sr 1-x )O] n [(Ti y Zr 1-y )O2] represents the component.

[0019] The dielectric particles may also include barium titanate.

[0020] The laminated electronic component of the present invention includes the above-mentioned dielectric. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 Schematic diagram showing a cross section of a multilayer ceramic capacitor.

[0022] Figure 2 This is a STEM-DF image of a cross section of a dielectric.

[0023] Figure 3 is a schematic diagram of a cross section of a dielectric.

[0024] Figure 4 is a schematic diagram of a cross section of a dielectric.

[0025] Explanation of symbols

[0026] 2…laminated ceramic capacitor, 4…element body, 4a…end face, 4b…side face, 10…ceramic layer, 12…internal electrode layer, 21…dielectric particles, 23a…segregation (special combination), 23b…segregation (not special combination), 25a…pores (special combination). DETAILED DESCRIPTION

[0027] In this embodiment, as an example of a laminated electronic component of the present invention, Figure 1 The multilayer ceramic capacitor 2 shown in FIG. 1 is described below. The multilayer ceramic capacitor 2 includes a device body 4 and a pair of external electrodes 6 formed on the outer surface of the device body 4 .

[0028] Figure 1 The shape of the component body 4 shown is generally a roughly rectangular parallelepiped, and has two end faces 4a opposite to each other in the X-axis direction, two side faces 4b opposite to each other in the Y-axis direction, and two side faces 4b opposite to each other in the Z-axis direction. There is no particular restriction on the outer dimensions of the component body 4. For example, the length L0 of the component body 4 in the X-axis direction can be set to 0.4mm to 5.7mm, the width W0 in the Y-axis direction can be set to 0.2mm to 5.0mm, and the height T0 in the Z-axis direction can be set to 0.2mm to 3.0mm. In this embodiment, the X-axis, the Y-axis, and the Z-axis are perpendicular to each other.

[0029] The element body 4 has a ceramic layer 10 and an internal electrode layer 12 that are substantially parallel to a plane including the X-axis and the Y-axis. Inside the element body 4, the ceramic layer 10 and the internal electrode layer 12 are alternately stacked along the Z-axis direction. Here, "substantially parallel" means that most of the parts are parallel, but there may be slightly non-parallel parts. The ceramic layer 10 and the internal electrode layer 12 may also be slightly uneven or inclined.

[0030] In addition, there is no particular limitation on the shape of the element body 4. Figure 1 In addition to the substantially rectangular parallelepiped shape shown, there are also elliptical columnar shapes, cylindrical shapes, prism shapes, and the like.

[0031] The ceramic layer 10 is composed of a dielectric described later. There is no particular restriction on the average thickness (interlayer thickness) of each layer of the ceramic layer 10. The average thickness of each layer of the ceramic layer 10 can be 100 μm or less, or 30 μm or less. In addition, there is no particular restriction on the number of stacking of the ceramic layer 10. The number of stacking of the ceramic layer 10 can be determined in accordance with the desired characteristics. The number of stacking of the ceramic layer 10 can be more than 20 layers, or more than 50 layers.

[0032] The internal electrode layers 12 are stacked between the ceramic layers 10. That is, the number of stacked internal electrode layers 12 is determined in accordance with the number of stacked ceramic layers 10. There is no particular limitation on the average thickness of each internal electrode layer 12. The average thickness of each internal electrode layer 12 may be 3.0 μm or less.

[0033] The average thickness of the ceramic layer 10 was observed using a metal microscope. Figure 1 The cross section shown in FIG. 1 is taken, and the thickness of each ceramic layer 10 is measured at least at 5 locations and averaged for calculation.

[0034] The average thickness of the internal electrode layer 12 was observed using a metal microscope. Figure 1 The cross section shown in FIG. 1 is taken, and the thickness of each internal electrode layer 12 is measured at least at five locations and averaged for calculation.

[0035] The internal electrode layer 12 is stacked in such a manner that one end is alternately exposed to two end faces 4a of the element body 4 that are opposite to each other in the X-axis direction. In addition, a pair of external electrodes 6 are respectively formed on one end face 4a of the element body 4, and are electrically connected to the exposed ends of the alternately arranged internal electrode layers 12. In this way, by forming the internal electrode layer 12 and the external electrode 6, a capacitor circuit is constituted by the external electrode 6 and the internal electrode layer 12. That is, the ceramic layer 10 existing in the capacitor region is sandwiched by the internal electrode layers 12 with different polarities, and a voltage can be applied to the ceramic layer 10.

[0036] The internal electrode layer 12 is made of a conductive material. The internal electrode layer 12 may contain Ni as a main component. The conductive material constituting the internal electrode layer 12 may be pure Ni, or a Ni-based alloy containing 85% by mass or more of Ni. In the Ni-based alloy, one or more elements selected from Mn, Cu, Cr, etc. may also be contained together with Ni. In addition to the above-mentioned conductive materials, the internal electrode layer 12 may also contain particles of a perovskite compound having the same composition as the main component of the ceramic layer 10 as a common material. The internal electrode layer 12 may also contain a trace amount of non-metallic components such as S or P. For example, it may contain less than 0.1% by mass. Furthermore, the internal electrode layer 12 may also contain voids.

[0037] When a common material or a void is included in the internal electrode layer 12 , a disconnected portion where no electrode (conductive material) exists may be formed in the internal electrode layer 12 .

[0038] A pair of external electrodes 6 may include a sintered electrode layer, a resin electrode layer, a plated electrode layer, etc. A pair of external electrodes 6 may be composed of a single electrode layer or may be composed of a plurality of stacked electrode layers. For example, the external electrode 6 may be a three-layer structure of a sintered electrode layer including Cu, a Ni plated layer, and a Sn plated layer (stacked in the order of the records). In the case of forming the external electrode 6 of the three-layer structure, since the Sn plated layer is located on the outermost surface of the external electrode 6, the solder wettability of the external electrode 6 is good.

[0039] In addition, if Figure 1 As shown, the external electrode 6 integrally includes an end face portion formed on the end face 4a in the X-axis direction of the element body 4, and an extension portion formed on the four side faces 4b of the element body 4 at the end portion in the X-axis direction. That is, a pair of external electrodes 6 are formed in a manner of wrapping around the side faces 4b from the end face 4a of the element body 4, and are insulated in a manner not to contact each other in the X-axis direction.

[0040] In addition, the extension of the external electrode 6 is not necessary, and the external electrode 6 may be composed of only the end surface. Alternatively, when the multilayer ceramic capacitor 2 is surface mounted on a substrate, the extension of the external electrode 6 may be formed at least on the side surface 4b opposite to the mounting surface of the substrate, and may not be formed on the side surface 4b on the opposite side of the mounting surface.

[0041] exist Figure 2, a cross-sectional photograph obtained by observing a cross section of a ceramic layer 10 containing the above-mentioned components, that is, a cross section of a dielectric constituting the ceramic layer 10, at a magnification of 50,000 times using STEM is shown. The dielectric constituting the ceramic layer 10 includes dielectric particles 21, segregation 23a, 23b, and pores 25a. The segregation 23a, 23b, and the pores 25a are included in the grain boundaries between two or more dielectric particles 21. In addition, SEM or the like may be used instead of STEM.

[0042] There is no particular limitation on the method of distinguishing the dielectric particles 21 , the segregations 23 a and 23 b , and the pores 25 a . Figure 2 This is a STEM-DF image obtained by STEM. In the STEM-DF image, the dielectric particles 21 appear brightest, and the pores 25a appear darkest. The segregations 23a and 23b appear to have brightness intermediate between the dielectric particles 21 and the pores 25a.

[0043] In order to more clearly distinguish the dielectric particles 21, segregation 23a, 23b and pores 25a, STEM-EDS can also be used for mapping analysis. By using the mapping image obtained by the mapping analysis together with the STEM-DF image, it is possible to distinguish more clearly. In the mapping image, according to the shade of the color, the area with a high existence ratio of the specified element, that is, the area of ​​segregation of the specified element, can be determined. In the element mapping image of the element contained in the segregation 23a, 23b, the segregation 23a, 23b looks thick. In contrast, the pore 25a looks light in the element mapping image of any element. In addition, STEM-WDS, SEM-EDX, or SEM-WDS can also be used instead of STEM-EDS.

[0044] The dielectric constituting the ceramic layer 10 has a special combination of segregation 23a and pores 25a in cross section. The dielectric constituting the ceramic layer 10 has a special combination, so that the sintering property of the dielectric is easily improved. Furthermore, the insulation resistance and durability of the dielectric are easily improved. In particular, cracks are less likely to occur in the dielectric.

[0045] Segregation 23b is a segregation that is not connected to the pores. Segregation 23b may not be included in the dielectric material constituting the ceramic layer 10. Figure 2 Pores that are not included in the dielectric material constituting the ceramic layer 10 but are not in contact with the segregation may also be included in the dielectric material constituting the ceramic layer 10 .

[0046] There is no particular limitation on the ratio of the number of specific combinations at the cross section of the dielectric material constituting the ceramic layer 10. For example, it may be 1.0×10 4 Pieces / mm 2 Above and 1.0×10 8 Pieces / mm 2Below, it can also be 1.2×10 4 Pieces / mm 2 Above and 3.9×10 7 Pieces / mm 2 Below, it can also be 2.0×10 4 Pieces / mm 2 Above and 5.0×10 6 Pieces / mm 2 By making the ratio of the number of the special combination within the above range, the sinterability of the dielectric is easily improved, and the insulation resistance and durability of the dielectric are easily improved. In particular, cracks are less likely to occur in the dielectric.

[0047] When calculating the ratio of the number of special combinations, the cross-section of the dielectric material constituting the ceramic layer is observed to be at least 1000 μm in total. 2 Furthermore, the number of special combinations existing in the observed cross section was confirmed, and the number ratio of the special combinations was calculated. In addition, in order to observe the cross section of the dielectric, a total of 1000 μm 2 As described above, multiple observation ranges can be set.

[0048] In the cross section of the dielectric, multiple pores 25a may be connected to one segregation 23a. In this case, the number of pores 25a connected to one segregation 23a is the number of special combinations. Multiple segregations 23a may be connected to one pore 25a. In this case, the number of segregations 23a connected to one pore 25a is the number of special combinations.

[0049] For the segregation 23a of the special combination, the number of pores 25a connected to the end of the long diameter side may be about 4 times or more than the number of pores 25a connected to the end of the short diameter side. Figure 2 In the figure, the pore 25a is in contact with the end of the long diameter side of the segregation 23a of the special combination.

[0050] There is no particular limitation on the particle size of the dielectric particles 21. The particle size of the dielectric particles 21 may be 5.00 μm or less, or 0.10 μm or more and 3.00 μm or less. In addition, there is no particular limitation on the average particle size of the dielectric particles 21. The average particle size of the dielectric particles 21 may be 5.00 μm or less, or 0.10 μm or more and 3.00 μm or less.

[0051] There is no particular limitation on the diameter of the segregation 23a, 23b. The diameter of the segregation 23a, 23b may be 5.00 μm or less, or 0.05 μm or more and 2.00 μm or less. In addition, there is no particular limitation on the average diameter of the segregation 23a, 23b. The average diameter of the segregation 23a, 23b may be 4.00 μm or less, or 0.04 μm or more and 1.50 μm or less.

[0052] There is no particular limitation on the diameter of the pores 25a. The diameter of the pores 25a may be 1.50 μm or less, or may be 0.01 μm or more and 0.50 μm or less. In addition, there is no particular limitation on the average diameter of the pores 25a. The average diameter of the pores 25a may be 1.00 μm or less, or may be 0.03 μm or more and 0.45 μm or less.

[0053] The value obtained by dividing the average diameter of the segregations 23a and 23b by the average diameter of the pores 25a may be 0.19 or more and 10.40 or less, may be greater than 1.00 and 6.00 or less, or may be 1.70 or more and 5.33 or less.

[0054] In particular, when the value obtained by dividing the average diameter of the segregations 23a and 23b by the average diameter of the pores 25a is greater than 1.00 and less than 6.00, the sinterability of the dielectric is easily improved, and the insulation resistance and durability of the dielectric are easily improved. In particular, cracks are less likely to occur in the dielectric.

[0055] In addition, the minimum diameter of segregation and pores is set to 1.0 nm. In other words, a portion with a diameter smaller than 1.0 nm is not considered as segregation or pores.

[0056] The particle size of the dielectric particles 21, the diameter of the segregation 23a, 23b and the diameter of the pore 25a can be measured by image analysis of the cross-sectional photograph. There is no particular restriction on the type of the cross-sectional photograph. It can be a cross-sectional photograph obtained using the above-mentioned STEM, or a cross-sectional photograph obtained using SEM, TEM, etc.

[0057] The particle diameter of the dielectric particle 21 is the equivalent circle diameter of the dielectric particle 21. The diameter of the segregation 23a, 23b is the equivalent circle diameter of the segregation 23a, 23b. The diameter of the pore 25a is the equivalent circle diameter of the pore 25a.

[0058] The equivalent diameter of a circle is the diameter of a circle of the same area.

[0059] The average particle size of the dielectric particles 21 can be calculated by measuring and averaging the equivalent circle diameters of at least 5 dielectric particles 21. The average diameter of the segregation 23a, 23b can be calculated by measuring and averaging the equivalent circle diameters of at least 5 segregation 23a, 23b. The average diameter of the pore 25a can be calculated by measuring and averaging the equivalent circle diameters of at least 5 pores 25a.

[0060] Comparing the diameter of the special combination of segregations 23a connected to each other and the diameter of the pores 25a of the special combination connected to the segregations 23a, the diameter of the pores 25a of the special combination may be smaller than the diameter of the special combination of segregations 23a.

[0061] There is no particular limitation on the composition of the dielectric particles 21. The dielectric particles 21 may contain a component containing Ca, Sr, and / or Ba as a main component. The dielectric particles 21 may also contain a perovskite compound represented by the general formula ABO3 as a main component. As perovskite compounds, barium titanate, calcium titanate, strontium titanate, calcium zirconate, strontium zirconate, calcium strontium zirconate, etc. are listed. The dielectric particles 21 may also contain barium titanate as a main component.

[0062] The dielectric particles 21 may also include a dielectric having a composition formula [(Ca x Sr 1-x )O] n [(Ti y Zr 1-y )O2] is the main component. In addition, the composition ratio is recorded based on the atomic number.

[0063] n represents the content ratio of site A to site B and may be 1.0 or more and 1.2 or less.

[0064] x represents the content ratio of Ca in the A site. x may be 0 or more and 1 or less.

[0065] y represents the content ratio of Ti in the B site. y may be greater than or equal to 0 and less than or equal to 0.3.

[0066] The element ratio of oxygen (O) in the above composition formula may slightly deviate from the stoichiometric composition.

[0067] The main component of the dielectric particles is a component contained in an amount of 95 mol % or more based on the entire dielectric particles.

[0068] There is no particular restriction on the composition of segregation. For segregation, in addition to O, Ca, Sr, Zr, and Ti, the element contained most on an atomic number basis may be Si. By containing more Si through segregation, the sintering property of the dielectric is easily improved. Furthermore, the insulation resistance and durability of the dielectric are easily improved.

[0069] Furthermore, assuming that the total area of ​​segregation in the cross section is 100%, the area ratio of segregation of Si, the element most contained on the basis of atomic number, other than O, Ca, Sr, Zr, and Ti, may be 25% or more in total.

[0070] The segregation may contain a Ca-Sr-Mn-Si-based component as a main component. The Ca-Sr-Mn-Si-based component may be an oxide. In addition, the component functions as a sintering aid.

[0071] The main component of the segregation is a component contained in 80 mol % or more based on the entire segregation.

[0072] The Ca—Sr—Mn—Si-based composition is a composition in which the total content of elements other than O is 100 mol % and the contents of Ca, Sr, Mn, and Si are each 3 mol % or more.

[0073] In the composition of the Ca-Sr-Mn-Si system, the total content of elements other than O is set to 100 mol%, and the content of Ca can be 20 mol% or more and 60 mol% or less. The content of Sr can be 10 mol% or more and 30 mol% or less. The content of Mn can be 3 mol% or more and 12 mol% or less. The content of Si can be 15 mol% or more and 45 mol% or less.

[0074] Segregation other than segregation containing Ca-Sr-Mn-Si system components as main components may be included in the dielectric constituting the ceramic layer 10. When the total area of ​​the segregation in the cross section is 100%, the area ratio of the segregation containing Ca-Sr-Mn-Si system components as main components may be 50% or more in total.

[0075] The linear expansion coefficient of the segregations 23 a and 23 b may be smaller than the linear expansion coefficient of the dielectric particles 21 .

[0076] The schematic diagram of the dielectric with a special combination is Figure 3 , the schematic diagram of the dielectric without special combination is Figure 4 .

[0077] Generally, if there is a portion with a relatively large linear expansion coefficient in a dielectric having dielectric particles and segregation, stress is applied from the portion with a large linear expansion coefficient to the portion with a small linear expansion coefficient. Furthermore, damage may occur in the dielectric.

[0078] Here, in order to sinter the dielectric at a low temperature, it is necessary to lower the sintering temperature by adding a sintering aid. However, if a sintering aid is added, segregation with a small linear expansion coefficient occurs.

[0079] In this case, if Figure 4As shown, compressive stress is applied from the dielectric particles 21 toward the segregation 23b (not a special combination). The direction of the arrow indicates the direction of the stress, and the size of the arrow indicates the size of the stress. Furthermore, cracks are easily generated in the dielectric due to the compressive stress.

[0080] Here, if Figure 3 As shown, if the pores 25a are adjacent to the segregation 23a in a manner having a special combination of the segregation 23a and the pores 25a, the compressive stress is relaxed. As a result, low-temperature sintering is facilitated and cracks are less likely to occur in the dielectric.

[0081] Next, Figure 1 An example of a method for manufacturing the multilayer ceramic capacitor 2 shown in FIG.

[0082] First, the manufacturing process of the element body 4 will be described. In the manufacturing process of the element body 4, a dielectric paste that becomes the ceramic layer 10 after firing and an internal electrode paste that becomes the internal electrode layer 12 after firing are prepared.

[0083] The dielectric paste is manufactured using a powder containing a component that becomes dielectric particles after firing (hereinafter, sometimes referred to as dielectric powder) and a segregation powder containing a component that becomes segregation after firing. Hereinafter, the case where the dielectric powder is composed of a perovskite compound and the segregation powder is composed of a Ca-Sr-Mn-Si-based oxide is described. However, there is no particular limitation on the composition of the dielectric powder and the composition of the segregation powder.

[0084] The dielectric powder can be manufactured by a solid phase method, a hydrothermal synthesis method, or a sol / gel method. For example, in the solid phase method, starting materials such as CaCO3 powder, SrCO3 powder, BaO powder, ZrO2 powder, and TiO2 powder are uniformly mixed by a wet mixing method, and then pre-calcined to obtain a dielectric powder composed of a perovskite compound. At this time, the pre-calcined dielectric powder can also be appropriately pulverized or classified.

[0085] The segregation powder is obtained by mixing a compound powder containing Ca (e.g., CaCO3 powder), a compound powder containing Sr (e.g., SrCO3 powder), a compound powder containing Mn (e.g., MnCO3 powder), and a compound powder containing Si (e.g., SiO2 powder) at a predetermined ratio and pre-calcining. The composition of the segregation can be controlled by the ratio of each compound powder as a starting material. In addition, when the segregation powder is manufactured, a crushing process or the like can be appropriately performed to control the diameter of the segregation. In addition, as each compound powder, oxide powder, carbonate powder, nitrate powder, sulfate powder, etc. can be used, and powders of compounds that become oxides after calcining can be used.

[0086] The dielectric paste is obtained by adding the above-mentioned dielectric powder and segregation powder to an organic carrier and kneading. The organic carrier is a substance obtained by dissolving a binder in an organic solvent. There is no particular limitation on the type of binder. It can be appropriately selected from well-known binders such as polyvinyl butyral, acrylic acid, and ethyl cellulose. There is no particular limitation on the type of organic solvent. It can be appropriately selected from well-known organic solvents such as methyl ethyl ketone, methanol, ethanol, acetone, toluene, terpineol, and butyl carbitol.

[0087] The above-mentioned dielectric paste is an organic coating. The dielectric paste can be a water-based coating obtained by kneading a mixed powder and a water-based carrier. The water-based carrier is prepared by dissolving a water-soluble adhesive or a dispersant in water. There is no particular limitation on the type of water-soluble adhesive. It can be appropriately selected from well-known water-soluble adhesives such as polyvinyl alcohol, water-soluble acrylic resin, and water-soluble polyvinyl butyral resin.

[0088] By adjusting the ratio of the dielectric powder and the segregation powder in the dielectric paste, it is possible to control the content ratio of the segregation in the finally obtained ceramic layer 10. The dielectric paste may also contain additives selected from various dispersants, plasticizers, dielectrics (other than perovskite compounds), glass frits, etc. as needed.

[0089] The internal electrode paste can be made by mixing conductive materials such as pure Ni powder or Ni alloy powder, organic metal compounds, and resinates with the above-mentioned organic carrier. Instead of the conductive material, various oxides that become the above-mentioned Ni or Ni alloy after firing can also be used. Furthermore, the dielectric powder contained in the dielectric paste can also be added to the internal electrode paste as a common material. The common material plays a role in suppressing the sintering of the conductive powder during the firing process.

[0090] Next, the dielectric paste is sheeted by a doctor blade method or the like to obtain a ceramic green sheet. Furthermore, the internal electrode paste is applied to the ceramic green sheet in a predetermined pattern by various printing methods such as screen printing or a transfer method. Furthermore, after the green sheets with the internal electrode pattern formed are stacked multiple times, they are pressed in the stacking direction to obtain a mother laminate. At this time, the ceramic green sheets and the internal electrode pattern are stacked in such a way that the ceramic green sheets are located on the upper and lower surfaces of the mother laminate in the stacking direction.

[0091] The mother laminate obtained through the above steps is cut into a predetermined size by dicing or cutting to obtain a plurality of green chips. The green chips may be cured and dried to remove the plasticizer and the like as necessary.

[0092] The green chip may be barrel-milled using a horizontal centrifugal barrel mill or the like. When the green chip is cured and dried, barrel-milling may be performed after the curing and drying.

[0093] In drum grinding, a green chip is placed in a drum container together with a medium and a grinding liquid. The green chip is drum-ground by rotating or vibrating the drum container. Unnecessary parts such as burrs generated during cutting are ground by drum grinding, and rounded corners (angle R) are formed at the corners of the green chip. The green chip after drum grinding is washed with a washing liquid such as water and dried. In addition, the drum grinding can also be implemented after the green chip is fired as described later.

[0094] Next, the green chip obtained by the above-mentioned method is subjected to a binder removal process and a firing process to obtain the element body 4 .

[0095] The conditions for the binder removal process may be appropriately determined in accordance with the composition of the dielectric particles, the composition of the segregation, the composition of the internal electrode layer, etc. For example, the heating rate may be set to 5 to 300° C. / hour, the holding temperature may be set to 180 to 400° C., and the holding time may be set to 0.5 to 24 hours. In addition, the binder removal atmosphere may be set to air or a reducing atmosphere.

[0096] The conditions of the sintering treatment can be appropriately determined according to the composition of the dielectric particles, the composition of the segregation, the composition of the internal electrode layer, etc. For example, the holding temperature during sintering can be set to 1200-1350°C, or 1220-1300°C. The holding time can be set to 0.5-8 hours, or 1-3 hours. In addition, the sintering atmosphere can also be set to a reducing atmosphere. As the atmosphere gas, for example, a mixed gas of N2 and H2 can also be humidified and used. Furthermore, in the case where the internal electrode layer is composed of a base metal such as Ni or a Ni alloy, the oxygen partial pressure in the sintering atmosphere can also be set to 1.0×10 -14 ~1.0×10 -10 MPa.

[0097] In addition, after the sintering treatment, an annealing treatment may be performed as needed. Annealing is a treatment for reoxidizing the dielectric contained in the ceramic layer. When the sintering treatment is performed in a reducing atmosphere, annealing is preferably performed. The conditions for the annealing treatment may be appropriately determined in accordance with the composition of the dielectric particles, the composition of the segregation, the composition of the internal electrode layer, etc. For example, the holding temperature may be set to 650 to 1150°C. The holding time may be set to 0 to 20 hours. The heating rate and the cooling rate may be set to 50 to 500°C / hour. The atmosphere gas may be dry N2 gas, humidified N2 gas, etc. In addition, the annealing treatment may be performed multiple times.

[0098] In the above-mentioned debinding treatment, firing treatment and annealing treatment, in order to humidify the N2 gas or the mixed gas, for example, a wetter can be used. When a wetter is used, the water temperature can be set to about 5 to 75° C. In addition, the debinding treatment, firing treatment and annealing treatment can be performed continuously or independently.

[0099] In each of the above-mentioned heat treatments (binder removal, sintering, annealing (reoxidation)), the green chip is placed on a setter, which is a plate-shaped refractory material, and heated. After the heat treatment, the fired element body 4 is dropped from the setter and recovered.

[0100] Next, a pair of external electrodes 6 are formed on the outer surface of the element body 4 obtained above. The method for forming the external electrodes 6 is not particularly limited. For example, in the case of forming a sintered electrode as the external electrode 6, after applying a conductive paste containing glass frit to the end face of the element body 4 by a dipping method, the element body 4 can be heated at a predetermined temperature. In addition, in the case of forming a resin electrode as the external electrode 6, a conductive paste containing a thermosetting resin is applied to the end face of the element body 4, and then the element body 4 is heated at a temperature at which the thermosetting resin is cured. Furthermore, after forming the sintered electrode or the resin electrode by the above method, electrolytic plating, electroless plating, sputtering, or evaporation, etc. can be performed to form the external electrode 6 having a multilayer structure.

[0101] Through the above-described steps, the multilayer ceramic capacitor 2 having the external electrodes 6 is obtained.

[0102] Hereinafter, three methods for producing the ceramic layer 10 including dielectrics having a special combination will be described. The method for producing the ceramic layer 10 including dielectrics having a special combination is not limited to the following three methods.

[0103] (First production method)

[0104] After the segregation powder is prepared and before the dielectric powder and the segregation powder are kneaded, a resin is attached to the segregation powder. If the type of the resin is a resin insoluble in an organic solvent or a resin poorly soluble in an organic solvent, there is no particular problem. As the resin attached to the segregation powder, polyvinyl alcohol (PVA) and the like are listed. PVA is a water-soluble resin and a resin insoluble in an organic solvent.

[0105] The amount of the resin to be deposited is not particularly limited, but may be 10 parts by mass or more and 100 parts by mass or less based on 100 parts by mass of the segregated powder.

[0106] The steps after the resin is attached to the segregated powder are as described above. During firing, the resin attached to the segregated powder disappears, pores are formed, and a special combination is generated.

[0107] (Second production method)

[0108] After the segregation powder is prepared and before the dielectric powder and the segregation powder are kneaded, the segregation powder and the carbon powder are mixed. There is no particular restriction on the mixing amount of the carbon powder. The segregation powder is set to 100 parts by mass, and can be 10 parts by mass or more and 100 parts by mass or less.

[0109] The process after mixing the segregated powder and the carbon powder is as described above. During firing, the carbon powder disappears, pores are formed, and a special combination is generated.

[0110] (Third production method)

[0111] When the segregated powder is produced, a spray dryer is used. By using the spray dryer to produce the segregated powder, at least a part of the obtained segregated powder has a hollow portion.

[0112] The steps after preparing the segregated powder having a hollow portion are as described above. During firing, the hollow portion becomes a void and a special combination is generated.

[0113] As mentioned above, although embodiment of this invention was described, this invention is not limited to the said embodiment at all, Various changes are possible within the range which does not deviate from the summary of this invention.

[0114] For example, in the present embodiment, the multilayer ceramic capacitor 2 is exemplified as the multilayer electronic component, but the multilayer electronic component of the present invention may be a bandpass filter, a multilayer three-terminal filter, a thermistor, a nonlinear resistor, or the like.

[0115] In addition, in the present embodiment, the ceramic layer 10 and the internal electrode layer 12 are stacked in the Z-axis direction, but the stacking direction may be in the X-axis direction or the Y-axis direction. In this case, the external electrode 6 may be formed according to the exposed surface of the internal electrode layer 12. In addition, the internal electrode layer 12 may be led to the outer surface of the element body 4 via a through-hole electrode. In this case, the through-hole electrode and the external electrode 6 are electrically connected.

[0116] [Example]

[0117] Hereinafter, the present invention will be described based on more detailed examples, but the present invention is not limited to these examples.

[0118] (Experimental Example 1)

[0119] Each capacitor sample shown in Table 1 described below was produced in the following procedure.

[0120] First, dielectric powder and segregation powder are prepared as raw materials of dielectric paste.

[0121] The solid phase method was used to prepare (Ca 0.70 Sr 0.30 )(Zr 0.96 Ti 0.04 )O3 powder. 0.70 Sr 0.30 )(Zr 0.96 Ti 0.04 )O3 powder is set as powder A.

[0122] In Experimental Example 1, powder A was used as dielectric powder. In addition, the above composition is described by atomic ratio. In addition, the composition of powder A is shared by all examples and comparative examples, and the particle size of powder A is such that the average particle size of dielectric particles in the finally obtained dielectric becomes the value shown in Table 1.

[0123] In addition, CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder were wet mixed at a predetermined ratio, and after pre-calcination, they were pulverized with a ball mill to produce segregation powder. In Experimental Example 1, a powder composed of Ca-Sr-Mn-Si oxides was used as the segregation powder. In addition, the particle size of the segregation powder was such that the average diameter ratio described later became the value shown in Table 1.

[0124] In the segregation contained in the finally obtained dielectric, the elements contained most on an atomic basis, other than O, Ca, Sr, Zr, and Ti, are the elements shown in Table 1. In addition, the segregation powders used for preparing samples other than Samples 14 and 15 all had the same composition.

[0125] The segregation powders used for the preparation of samples other than samples 14 and 15 were prepared in such a way that the ratio of CaCO3 powder, SrCO3 powder, MnCO3 powder and SiO2 powder was Ca:Sr:Mn:Si=0.86:0.57:0.57:1.00 in molar ratio. The segregation powders used for the preparation of sample 14 were prepared in such a way that the ratio of MnCO3 powder and MgCO3 powder was Mn:Mg=0.40:0.60 in molar ratio. The segregation powders used for the preparation of sample 15 were prepared in such a way that the ratio of CaCO3 powder, SrCO3 powder, Al2O3 powder and SiO2 powder was Ca:Sr:Al:Si=1.6:0.4:2.0:1.0 in molar ratio.

[0126] Next, 35.75 parts by mass of the dielectric powder, 0.50 parts by mass of the segregated powder, 0.25 parts by mass of PVA, and 63.50 parts by mass of the organic vehicle were kneaded to obtain a dielectric paste.

[0127] Separately, 50.63 parts by mass of Ni powder, 10.12 parts by mass of dielectric powder, and 39.25 parts by mass of an organic vehicle were kneaded to obtain an internal electrode paste.

[0128] Furthermore, as the above-mentioned organic carrier, ethyl cellulose was used.

[0129] Next, the above-mentioned dielectric paste and internal electrode paste are used to manufacture green chips by a thin-sheet method. Furthermore, the green chips are subjected to a binder removal process, a sintering process, and an annealing process to obtain a component body 4 (capacitor sample) having a size of L0×W0×T0=3.2mm×2.5mm×2.5mm. In addition, in the obtained component body 4, the number of stacked ceramic layers 10 sandwiched by the internal electrode layers 12 is set to 150, the average thickness of the ceramic layers 10 is set to 12μm, and the average thickness of the internal electrode layers 12 is set to 1.4μm.

[0130] The conditions for the binder removal treatment were set at 260° C. for 8 hours, the conditions for the calcination treatment were set at 1240° C. for 2 hours, and the conditions for the annealing treatment were set at 750° C. for 2 hours.

[0131] In sample number 1, segregation powder and PVA were not used. In sample number 2, PVA was not used. In sample number 3, segregation powder was not used. In sample number 4, PVA was added after mixing dielectric powder, segregation powder and organic carrier. In sample numbers 5 to 19, after making part or all of PVA adhere to segregation powder, dielectric powder, segregation powder and organic carrier were mixed, and PVA not adhered to segregation powder was further added. In addition, in order to control the number ratio of special combinations to the value shown in Table 1, the ratio of the amount of PVA adhered to segregation powder and the amount of PVA not adhered to segregation powder was controlled.

[0132] The following evaluations were performed on each capacitor sample of Experimental Example 1.

[0133] The segregation phase existing in the ceramic layer was analyzed by STEM-EDS.

[0134] First, a thin-slice sample was taken from the ceramic layer 10 located near the center of the element body by a micro-sampling method using a focused ion beam (FIB) (JIB-4700F manufactured by JEOL Ltd.). Specifically, the ceramic layer 10 was roughly cut at 30 kV-0.3 nA, and then the ceramic layer 10 was processed into a thin-slice sample of about 12 μm×10 μm×100 nm at 30 kV-100 pA. In addition, cross-section cleaning was performed at 5 kV-70 pA.

[0135] Next, the cross section of the thin sample was observed using STEM-EDS (JEM-2200FS (HR) manufactured by JEOL Ltd.). The observation magnification of STEM-DF images was 50,000 times and the accelerating voltage was 200 kV. For elemental mapping, PHA was set to T2, the counting rate was set to about 15,000 to 25,000 cps, the effective time (live time) was set to about 1,500 seconds, the number of pixels was set to 256×256, and the scan count was set to 200.

[0136] The size of the observation range of the STEM image was set to 10μm×10μm per site, and four different sites were observed. The STEM-DF images and element mapping of the four sites were used to confirm the presence of segregation, the presence of pores, and the presence of special combinations, and the number ratio of special combinations was calculated. In addition, the type of element that is most contained in the segregation based on the atomic number (the most segregated element) was confirmed, except for O, Ca, Sr, Zr, and Ti.

[0137] In addition, if there is a part where it is difficult to judge whether the segregation and the pore are connected, the periphery of the part is expanded to a size of 2μm×2μm in the observation range and judged. Even if one dot is connected to each other, the segregation and the pore are connected, and if one dot is not connected, the segregation and the pore are not connected.

[0138] The average diameter of segregation and the average diameter of pores are calculated, and the value obtained by dividing the average diameter of segregation by the average diameter of pores (average diameter ratio) is calculated. Furthermore, the average particle size of dielectric particles (dielectric particle size) is calculated.

[0139] In all the Examples and Comparative Examples, it was confirmed that the diameter of the pores of the specific combination was smaller than the diameter of the segregation of the specific combination.

[0140] Regarding the resistivity (IR), the insulation resistance of each sample was measured at a reference temperature (25°C) using a digital resistance meter (R8340 manufactured by ADVANTEST). The resistivity (IR) was calculated from the obtained insulation resistance, effective electrode area, and dielectric thickness. The results are shown in Table 1. IR was 1.00×10 11 Ω or above is considered good, and 1.00×10 13 Ω or more is considered better. In addition, the IR of sample number 5 is indicated as 1.82E+13 in Table 1. This means that 1.82×10 13 .

[0141] In Experimental Example 1, for the resistivity less than 1.00×10 11 In the case of Ω, the crack occurrence rate was not evaluated.

[0142] For a resistivity of 1.00×10 11 For each sample with a crack generation rate of Ω or above, an evaluation is performed on the crack generation rate. First, 100 capacitor samples for each sample number for crack generation rate evaluation are made. Then, for the made capacitor samples, confirm whether there are cracks in the dielectric. Then, for the made capacitor samples, PCT (Pressure Cooker Test) is performed. The conditions of PCT are set to 121°C and 95% RH. For the capacitor samples after 24 hours of PCT, confirm whether there are cracks in the dielectric. Finally, for the capacitor samples after 24 hours of PCT, PCT is further implemented so that the implementation time of PCT is a total of 168 hours. For the capacitor samples after a total of 168 hours of PCT, confirm whether there are cracks in the dielectric. The results are shown in Table 1.

[0143] For capacitor samples before PCT implementation, the crack generation rate was 1% or less, that is, the case where one or less capacitor samples had cracks was considered good. For capacitor samples after PCT implementation for 24 hours, the crack generation rate was 10% or less, that is, the case where ten or less capacitor samples had cracks was considered good. For capacitor samples after PCT implementation for 168 hours, the crack generation rate was 40% or less, that is, the case where 40 or less capacitor samples had cracks was considered good.

[0144] The overall crack generation rate before PCT, 24 hours after PCT, and 168 hours after PCT was performed was less than 1%, that is, the case where cracks were not generated in all capacitor samples was considered to be more favorable.

[0145] In all embodiments and comparative examples, it is confirmed that the linear expansion coefficient of segregation is smaller than the linear expansion coefficient of dielectric particles. First, a sintered body is prepared using only the above-mentioned dielectric powder. The sintered body prepared using only the dielectric powder has the same composition as the above-mentioned dielectric particles. In addition, a sintered body having the same composition as the composition of the segregated phase is prepared. Furthermore, the average linear expansion coefficient of each sintered body is measured and confirmed. In addition, the average linear expansion coefficient of each sintered body is measured in the range from room temperature to 1200°C using thermomechanical analysis (TMA).

[0146]

Table 1

[0147]

[0148] From Table 1, the capacitor samples of each sample number including dielectrics having a special combination have high resistivity IR. Moreover, although the resistivity IR is equal to or higher than that of the capacitor samples of sample numbers 2 and 4 including dielectrics having no special combination, it is difficult to generate significant cracks.

[0149] (Experimental Example 2)

[0150] Experimental Example 2 was conducted under the same conditions as Sample Nos. 5 and 16 to 19 of Experimental Example 1 except that the dielectric powder was barium titanate (Powder B) (Sample Nos. 20 to 24). The results are shown in Tables 2 and 3. In addition, when Powder B was used, the IR changed greatly compared to the case of using Powder A, so the IR was not recorded in Tables 2 and 3. However, it was confirmed that the IR of Sample Nos. 20 to 24 was of the same level.

[0151]

Table 2

[0152]

[0153]

Table 3

[0154]

[0155] Tables 2 and 3 show that even when the composition of the dielectric powder, that is, the composition of the dielectric particles, is changed, it is difficult for the capacitor sample including the dielectric having a specific combination to significantly crack.

Claims

1. A dielectric, wherein: Contains dielectric particles, segregation and pores, At the cross section, there is a special combination of the segregation and the pores meeting.

2. The dielectric according to claim 1, wherein The diameter of the pores of the particular combination is smaller than the diameter of the segregation of the particular combination.

3. The dielectric according to claim 1 or 2, wherein: The value obtained by dividing the average diameter of the segregation by the average diameter of the pores is greater than 1.00 and is 6.00 or less.

4. The dielectric according to claim 1 or 2, wherein: The number ratio of the special combination at the cross section of the dielectric is 2.0×10 4 Pieces / mm 2 Above and 5.0×10 6 Pieces / mm 2 the following.

5. The dielectric according to claim 1 or 2, wherein: The linear expansion coefficient of the segregation is smaller than the linear expansion coefficient of the dielectric particles.

6. The dielectric according to claim 1 or 2, wherein: In addition to O, Ca, Sr, Zr, and Ti, the element contained in the largest amount on the basis of atomic number in the above segregation is Si.

7. The dielectric according to claim 1 or 2, wherein: The particle diameter of the dielectric particles is not less than 0.10 μm and not more than 3.00 μm.

8. The dielectric according to claim 1 or 2, wherein: The dielectric particles include a composition formula of [(Ca x Sr 1-x )O] n [(Ti y Zr 1-y )O2] represented by the component.

9. The dielectric according to claim 1 or 2, wherein: The dielectric particles include barium titanate.

10. A laminated electronic component, wherein: A dielectric according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Multilayer ceramic capacitor

    JP2004273975A